The effectiveness of individual counseling in improving discipline students with action research - Mairoza, Andra; Sandra, Rober; Fitriani, Wahidah (Jurnal Aplikasi IPTEK Indonesia, 2022)
This study aims to see and analyze the improvement of student discipline through individual counseling services at SMK Negeri 1 Gunung Talang. This research is a Classroom Action Research which consists of two cycles, each cycle consists of: planning, action, reflection, and evaluation. The data is processed in each cycle and then analyzed using percentages. The results obtained from this study conclude that individual services can improve student discipline. This conclusion is based on the results obtained in the first cycle of Individual Counseling. In this activity, student discipline increased by 17.8% from the pre-cycle. The results of the first cycle of research, the second cycle of actions was carried out. Student discipline increased by 3.47%. From this research, it can be concluded that individual service can improve student discipline. This research can be used as literature for further research, useful as an effort to overcome student discipline problems and to find out the extent of changes that occur in the discipline of class X students at SMK Negeri 1 Gunung Talang. Research Results In pre-cycle I, stated that students who were late reached 54 students in class X at SMK 1 Negeri Gunung Talang. After the first cycle of action, the students who were late decreased to 16 people. From the results of the first cycle of data, the second cycle of action was carried out, the results obtained after taking the student's action were no longer late in class X SMK Negeri 1 Gunung Talang.